Implikasi Prilaku-Prilaku Organisasi Terhadap Kinerja Karyawan di Lembaga Pendidikan - Azhar, Imam (Darajat: Jurnal Pendidikan Agama Islam, 2023)
This study aims to investigate the impact of organizational commitment of workers, jobsatisfaction and job discipline towards employees’ performances. It has been proven throughprevious literature that organizational commitment is defined as the relative strength of anindividual’s recognition with, and participation in an organization. The concept of the jobsatisfaction consists of the feelings and attitudes one has about one’s job. These attitudesinclude all aspects of negative or positive feelings about a particular job wihc are likely tocontribute to the development of feelings of satisfaction (or dissatisfaction), while jobdiscipline is an effort of the management of the institution to implement or execute the rulesor regulations that must be adhered by all employees without exception. The data wascollected from 127 employees using stratified random sampling and used path analysis. Therisults of the study shown that: organizational commitment has positive direct effect toward  employees’ performance (β=0,658); organizational commitment has positive direct effecttoward job discipline (β=0,862); Job discipline doesn’t have direct effect toward employees’performance (β=-0.022); Job Satisfaction has direct effect toward employees’ performance(β=0.943); Organizational commitment has direct effect toward employees’ performancethrough job satisfaction (β = 0,862); Job discipline doesn’t have direct effect towardemployees’ performance through job satisfaction (β=-0.022); organizational commitment hasdirect effect toward employees’ performance (β=0.943); and Job discipline hasn’t direct effecttoward employees’ performance (β = 0,162)